A profile of hematological malignancies diagnosed in a tertiary care center of Assam: Highlighting the experience from a resource constraint perspective - Gogoi, Gayatri; Nivarani Dutta; Sima Sonowal; Anjanjyoti Rajkonwar; Bhabesh Dehingia; Subhalakhimi Saikia; Sudeshna Borgohain (Asian Journal of Medical Sciences, 2023)
Background: Hematological disorders require a systematic approach, from clinical examination to a complete blood count, followed by a bone marrow study for diagnosis. To effectively plan, treat, and prognosticate, immunophenotyping and molecular studies are essential to incorporate. Aims and Objectives: The aim of our study is to understand the pattern of neoplastic hematological conditions encountered in Assam and share our experience during the diagnosis. Materials and Methods: This was a single-centered, observational study carried out for 18 months (January 2022–June 2023). A thorough hematological workout was done, including cytochemical staining and conventional polymerase chain reaction for the BCR-ABL transcript, after satisfying inclusion and exclusion criteria. The data were analyzed and correlated before arriving at the final diagnosis. Results: The total of 38 neoplastic cases confirmed by bone marrow study. Out of 38 cases, 14 were chronic myeloid leukemia, 10 were chronic, 4 were in the blastic phase, and BCR-ABL was positive in 13 cases. Two cases were pediatric, of which 1 was in the blastic phase. All 8 cases of plasma cell dyscrasia presented with anemia, bone lesions, and hypercalcemia. The acute leukemia category consisted of 4 acute myeloid leukemia cases, of which 1 was acute promyelocytic leukemia. A total of 10 acute lymphoblastic leukemia (ALL) cases, where 1 case was T-ALL and the rest was B-ALL. Two cases showed a subleukemic presentation in peripheral blood. Conclusion: The experience of pathologists and their meticulous approach can greatly aid in accurate diagnosis, but the immunophenotyping facility and molecular hematology setup can provide most of the relevant information for the best decision-making.